A novel pathway toward efficient and stable C3N4-based photocatalyst for light driven H2 evolution: The synergistic effect between Pt and CoWO4. (25th October 2019) - Xue, Mengru; Bao, Xiaoluo; Li, Xiangqing; Qin, Lixia; Han, Sheng; Kang, Shi-Zhao
Abstract: A photocatalytic integrated system containing Pt nanoclusters, CoWO4 nanoclusters and C3 N4 nanosheets was achieved through a hydrothermal process followed by photodeposition. Meanwhile, the photocatalytic activity of the as-prepared system was explored for light driven H2 evolution. Finally, the photocatalytic mechanism was explored roughly. The results show that there exists strong synergistic effect between Pt and CoWO4 . The photocatalytic activity of C3 N4 can be significantly enhanced utilizing the aforementioned synergistic effect. When the as-prepared photocatalytic system is used, the fastest evolution rate of H2 can be up to 14.2 μmol h −1, which is 2.1 times as high as that over the Pt modified C3 N4 nanosheets (6.7 μmol h −1 ). And the quantum yield of the as-prepared photocatalytic system at 400 nm (0.018%) is also much higher than that of the Pt modified C3 N4 nanosheets (0.004%). Here, this remarkable photocatalytic activity ought to be attributed to superior separation of the electro-hole pair caused by efficient charge transfer in the photocatalytic system which follows a Z-scheme-like mechanism. Therein, Pt nanoclusters may serve as an electron transfer pathway between CoWO4 and C3 N4 as well as active sites while CoWO4 nanoclusters may play a water oxidation cocatalyst. Graphical abstract: Dramatic enhancement of photocatalytic activity of C3 N4 via synergistic effect of Pt and CoWO4 : A novel pathway toward efficient and stable C3 N4 -based photocatalyst for light driven H2 evolution. Mengru Xue, Xiaoluo Bao, Xiangqing Li, Lixia Qin, Sheng Han, Shi-Zhao Kang.Image 1 Highlights: Novel pathway toward efficient and stable C3 N4 -based photocatalyst for H2 evolution. A photocatalytic system containing Pt, CoWO4 and C3 N4 . Enhance photocatalytic activity of C3 N4 via synergistic effect of Pt and CoWO4 .